THE COURSE OF PREGNANCY AND CHILDBIRTH IN A WOMAN WITH LARGE UTERINE FIBROIDS - Нонна Марковна Шибельгут; Наталья Анатольевна Батина; Алена Васильевна Иванникова; Полина Андреевна Овчарова; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес (The Publishing House Medicine and Enlightenment, 2023)
Uterine fibroids are the most common benign tumor of the female reproductive system. The incidence of the disease among women of reproductive age reaches 70%. In most women, the disease is asymptomatic, which makes it difficult to assess the true prevalence. In some cases, uterine fibroids do not prevent the onset of pregnancy and fetal development, but increase the frequency of complications of pregnancy and childbirth. During pregnancy, an ultrasound examination should be performed to assess the condition of the fetus and pelvic organs. Indications, access and scope of surgical intervention are determined by commission (by decision of the medical council). This publication is devoted to the delivery of a woman with large uterine fibroids.